Strategi Menjaga Keharmonisan Rumah Tangga Jarak Jauh Perspektif Pesepak Bola Profesional Klub Jakarta Matador FC - Ainur Rofiq (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2020)
Marriage is a form of uniting two servants of God into the same goal, the purpose of marriage is to achieve lasting happiness with a spouse. However, it cannot be denied that career demands have forced the footballer family at the Jakarta Matador FC Club to have long-distance relationships. The purpose of this study was to determine the conditions and household strategies of the married couples of professional footballer families in the Jakarta Matador FC club who have long-distance relationships and are still able to maintain harmony. Then it also aims to find out a review of Islamic law on long-distance households in the married couples of professional footballer families at the Jakarta Matador FC Club. This study used a qualitative approach with descriptive qualitative research with the location of the research on the married couples of footballers who live in Jember and Banyuwangi. Primary data sources are interviews with married couples of professional footballer families at the Jakarta Matador FC club who have long-distance relationships and secondary data, namely other literature relevant to the issues being studied. Data collection methods are observation, interview, and documentation. Meanwhile, the qualitative descriptive data analysis method starts from data reduction, data presentation and concluding. The data validity used source and technique triangulation. The results of this study explain that although the distance is separated, the footballer family can be said to be harmonious because of the openness, mutual trust and good communication among them. Based on the theory of maqasid syari'ah, long distance relations carried out by research subjects have carried out their rights and obligations until they are generally allowed.